2006
DOI: 10.1590/s0021-75572006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do pico de pressão, do volume corrente e da freqüência respiratória durante ventilação de carneiros prematuros utilizando balão auto-inflável

Abstract: Objective: To evaluate the peak inspiratory pressure, tidal volume and respiratory rate achieved during manual ventilation of premature lambs, using a self-inflating bag. Methods:In this descriptive, experimental study, five pairs of physicians, selected at random among 35 neonatologists working at a neonatal intensive care unit and with experience in the resuscitation of newborn infants, ventilated five intubated premature lambs using a self-inflating bag. Pressure and flow monitor signals were passed through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
(13 reference statements)
0
4
1
2
Order By: Relevance
“…We also found that nearly half of the participants delivered breaths at insufficient rates (Ͻ 40 breaths/min), in contrast with the findings by Rezende at al, 17,18 who showed good adequacy for f. This discrepancy is possibly due to differences in the volunteer population. Rezende et al 17,18 studied a small group of experienced physicians, whereas we studied a larger sample of subjects from 5 different professions who work with neonatal intensive care, with variable experience in resuscitation.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…We also found that nearly half of the participants delivered breaths at insufficient rates (Ͻ 40 breaths/min), in contrast with the findings by Rezende at al, 17,18 who showed good adequacy for f. This discrepancy is possibly due to differences in the volunteer population. Rezende et al 17,18 studied a small group of experienced physicians, whereas we studied a larger sample of subjects from 5 different professions who work with neonatal intensive care, with variable experience in resuscitation.…”
Section: Discussioncontrasting
confidence: 81%
“…18 Both studies showed wide variability of delivered pressures and volumes, which frequently exceeded standard values for safe ventilation. 17,18 The present study shows that the high variability does not seem to be an artifact due to restricted sample size, because it was still observed even with a considerably greater number of volunteers (n ϭ 172).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Isso resulta em lesão pulmonar por vários mecanismos, incluindo a exposição a elevadas concentrações de oxigênio, o atelectrauma e o volutrauma (3) . Neste sentido, os resultados publicados por Zaconeta et al (4) nesta edição da Revista Paulista de Pediatria têm o mérito de acrescentar mais informação a este assunto produzida por um grupo com tradição em pesquisa nesta área (5,6) . Um dos pontos fortes do trabalho é o estudo de uma população pouco avaliada na literatura pediátrica: profissionais não-médicos que atuam na linha de frente das emergências ocorridas com crianças fora do ambiente hospitalar.…”
unclassified